Diffuse glomerulonephritis, in the period of 1945-1956, in the services of the first chair of clinical medicine, medical and therapeutic nosography. - Toledo, Julio (1957)
The observations presented here are based on the study of patients with glomerulonephritis Diffuse, served in the Services "Julian Arce" and "Abel Olaechea" Hospital May 2, directed by Prof. Dr. Sergio Benales in understanding decade 1945 to 1956. As the title indicates, this analysis relates only to the clinical appearance of these patients.